The profession of dramatist in Shakespeare's time, 1590-1642 - Bentley, Gerald Eades, 1901-1994 (Princeton, New Jersey ; Guildford, England : Princeton University Press, 1984)
Gerald Eades Bentley assembles and analyzes the extant theatrical materials of the sixteenth and seventeenth centuries. His discussion of the working conditions of professional dramatists like Thomas Heywood, John Fletcher, and Philip Massinger as well as William Shakespeare rounds out the fascinating picture of the professionalism that developed in the great days of Elizabethan and Jacobean theatre.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface -- Contents -- I. Introduction -- II. Amateur Dramatists and Professional Dramatists -- III. The Status of Dramatists, Plays, Actors, and Theatres -- IV. The Dramatist and the Acting Company -- V. Dramatists' Pay -- VI. Dramatists' Contractual Obligations -- VII. Regulation and Censorship -- VIII. Collaboration -- IX. Revision -- X. Publication -- Index -- Front Matter 2 -- Contents -- Preface -- I. Introduction -- II. The Player and His Company -- III. Sharers -- IV Hired Men -- V. Apprentices -- VI. Managers -- VII. London Companies on Tour -- VIII. Casting -- IX. Conclusions -- Appendix: Casts and Lists of Players -- Index
"First Princeton Paperback printing, 1986"--Title page verso
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Shakespeare, William, -- 1564-1616 -- Contemporaries; Shakespeare, William, -- 1564-1616; Playwriting -- History -- 17th century; Dramatists, English -- Early modern, 1500-1700 -- Biography; Theater -- England -- History -- 17th century; English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism; English drama -- 17th century -- History and criticism; Création dramatique -- Histoire -- 17e siècle.; Théâtre -- Angleterre -- Histoire -- 17e siècle.; Théâtre anglais -- 16e siècle -- Histoire et critique; Théâtre anglais -- 17e siècle -- Histoire et critique; DRAMA -- European -- English, Irish, Scottish, Welsh; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; DRAMA -- English, Irish, Scottish, Welsh; Contemporaries; Dramatists, English -- Early modern -- Biography; English drama; English drama -- Early modern and Elizabethan; Playwriting; Theater; England; 1500-1699; Biographies; Criticism, interpretation, etc; History; Biographies; Biographies